KORELASI PEMBANGUNAN INFRASTRUKTUR KE-PU-AN TERHADAP PENINGKATAN KONDISI SOSIAL EKONOMI MASYARAKAT PASCABENCANA DI PROVINSI NANGROE ACEH DARUSSALAM - F.X. Hermawan Hermawan Kusumartono (Widyariset, 2009)
This paper described the relation ofp ublic work infrastructures after disaster and the increasing ofp eople welfare in Nangro Aceh Darussalam (NAD) Province. This matter was based on the fact that there was not seen in advance, how much disaster influenced the condition ofp eople's economy. This condition was the main targets as receivers of the benefit. The increasing of people welfare was measured from education, income, job, and possession. This research used the combination of two methods, namely the qualitative and the quantitative methods (Mix Method). The qualitative method was used to answer social factor questions affecting the optimization of the public work infrastructures on the disaster area. The quantitative method was for observing and measuring people's economic condition level that changed then compared with disaster happened before. The research used six sample villages in the NAD Province. The observation found that the public work infrastructures were implemented in rehabilitation and reconstruction stage and it affected on the increasing of people's economy. There were some social problems in the process of planning and implementing stage. This condition caused less optimal public work infrastructures. Therefore, the study suggests that it needs some steps to anticipate against social problems, subsequently public work infrastructures could be well implemented and could increase people welfare.